ANALYSIS OF LEADERSHIP STYLE AND COMPETENCE ON TEACHER PRODUCTIVITY WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLEAT PERMATA 2 STATE MIDDLE SCHOOL IN BENER MERIAH REGENCY - Hafnidah; Mesra B; Sri Rahayu (RADJA PUBLIKA, 2025)
This research investigates the influence of leadership style and competence on teacher productivity, with organizational commitment acting as an intervening variable. The study was conducted at SMP Negeri 2 Permata in Bener Meriah Regency, involving 81 teachers. A quantitative approach was employed, utilizing a saturated sample. Results indicate that leadership style has a positive and significant impact on both teacher productivity and organizational commitment. Competence, however, showed a positive but insignificant direct effect on teacher productivity. Organizational commitment significantly mediates the relationship between leadership style and competence with teacher productivity. The study recommends that school leaders maintain clear instructions and that internal supervision be conducted periodically with constructive feedback to improve teacher productivity.